Appraisal of Farm Mechanization and Farmer’s Field Practice of Maize Farming at Lamahi Municipality, Dang, Nepal - Jha, Prabhat; Marahatta, Santosh (Journal of Agriculture and Environment, 2023)
The study compares farm mechanization and farmer’s field practice to document the agronomic and economic feasibility of mechanized maize farming. The research was carried out in randomized complete block design with 2 treatments of mechanized practice and farmers practice and 3 replications as location for the winter maize using 10v10 hybrid variety. In agronomic aspect, seed rate and urea application in farmers practice (17.05 kg ha-1 and 186.41 kg ha-1 respectively) were found lower to mechanized practice (30.00 kg ha-1 and 348.00 kg ha-1 respectively). Consequently, lower yield was found in farmers practice (7.56 t ha-1) to mechanized practice (10.43 t ha-1) which was attributed by lower plant population, higher sterility, and smaller cob diameter in farmers’ practice. The benefit cost ratio was higher in mechanized practice (3.76) to farmer’s practice (2.44). Labour shortage can be mitigated by mechanization through the custom hiring center even in small holder maize growers.